Taqiyyah, Language and Game: On Lawrence Abu Hamdan's Contra Diction: Speech against itself. (3rd July 2016) - You, Mi
Abstract : Aptly combining video, installation and performative formats, Lawrence Abu Hamdan has created a rich body of works that often reveal the political dimension of language and speech. The article investigates, in particular, the live performative lectureContra Diction: Speech against itself, which draws ontaqiyyah, an old esoteric Shi'a Islamic jurisprudence practised by the Druze Islamic minority, whereby 'a believing individual can deny his faith or commit otherwise illegal acts while they are at risk of persecution or in a condition of statelessness'. The artist analyses various moments involving language and speech act in the Druze community, such as in the Islamic conversion and the communication between mother and baby through the lens oftaqiyyah, which reveals the paradoxical structure of language and language in its pre-semantics instance. Similar to games that are dynamic, the application oftaqiyyah suggests transformations of rules that challenge the structural divide between form of expression and form of content in language. Furthermore, drawing on Massumi's notion of 'non-sensuous similarity', the alignment oftaqiyyah to the 'sense-perceived meaning' highlights the dynamics of the immanence that constantly differentiates into language and expression. This leads to a conceptual comparison to Deleuze and Guattari's interpretation of the gameGo, which reveals howtaqiyyah may be seen to reclaim a consciousness pertinent to the smooth space, hence avidly transforming the condition of language.